Relationship between feeding development and alterations in orofacial motor skills (2022)
Introduction: The orofacial system is an anatomicalfunctional unit that enables the human being to perform various functions essential for life. It consists of oral structures, static and dynamic structures, and its harmonious functioning is based on the balanced relationship between its parts. Method: A systematic review was carried out to find out the relationship between feeding development and orofacial motor disturbances. As a search strategy, equations were formulated with selected descriptors MESH and DECS (“feeding, infancy”, “orofacial motricity”, “phonoaudiology”, “pediatrics”), the databases consulted were Pubmed, Science Direct, Scopus, Redalyc, Dialnet, Scielo, Proquest, World wide science, Biomed Central, Red Iberoamericana de Innovación y Conocimiento Científico, Semantic Scholar, Revista Javeriana. The PRISMA methodology was used to locate, collect, analyze and synthesize the information. The criteria for inclusion in the sample were publications that addressed the study interest, in children from 0 months to 12 years of age suffering from brain alterations or pathologies; articles published in the last 10 years in Spanish, English, and Portuguese. Publications not related to mode and type of feeding, orofacial motor skills, and those whose population was contrary to the required characteristics were excluded. Results: A total of 1 058 667 studies were found, after screening, eligibility, and full-text review, 53 documents were selected corresponding to studies published from 2011 to 2021, related to the alterations of the orofacial structures and the factor associated with intervention type and feeding mode. Analysis and Discussion: Exclusive breastfeeding and suckling favor the swallowing process and strengthen all orofacial muscles, the difficulties that may occur in the different orofacial functions are rooted in a mechanical process that should be consolidated in the first days of life. Significant alterations of the facial structures are closely linked to orofacial myofunctional alterations, emphasizing the presence of craniofacial complexes. Conclusions: Possible alterations in the orofacial complex may originate from bad oral habits that affect anatomy and physiology. Since feeding is a process that unquestionably involves the functional exercise of the orofacial system, several risk factors are evidenced in relation to the functioning that implies multidisciplinary intervention directed to parents and caregivers. Keywords: Nutrition, childhood, orofacial motor skills, speech therapy, pediatrics.